Evaluation of the thermal performance of construction systems to reduce the energy consumption in buildings: A case study in a cold semi-arid climate - Rodríguez Muñoz, Norma Alejandra (Acta Universitaria, 2020)
The performance of a three-story laboratory building was analyzed to reduce its annual energy consumption. The analysis was performed through a whole-building simulation approach and dynamic simulations to calculate the potential reduction of heating and cooling energy requirements by evaluating various construction systems. The main objective was to accomplish a decrease in energy consumption without the implementation of sophisticated constructive systems, which are commonly unavailable or unfeasible to apply in developing countries. Therefore, a two-stage analysis was carried out. At the first stage, a set of commonly available construction materials were implemented. From this analysis, it was shown that the use of an insulated concrete wall, double tinted glass, and an insulated terracotta roof corresponds to the optimal combination of materials, resulting in a decrease of 36% on the total annual energy requirements. Finally, from the second stage analysis, where double-wall systems and a green façade were implemented, an additional energy saving of up to 16% was achieved.